Open Economy or Protectionism: Ukraine’s Dilemma - Anton Oleinik (Montenegrin Journal of Economics)
Since 1991, Ukraine has had several economic crises (1991-1999, 2009, ongoing since 2014) and a period of economic boom from 2000 to 2008. The current crisis has external (the unfavorable situation in the world commodities markets) and internal (the military conflict with neighboring Russia) dimensions. The destruction of economic infrastructure and the unpreparedness of Ukrainian producers to compete globally explain its depth and complexity. Radical and non-orthodox measures may be needed to help Ukraine to return to economic growth. This article discusses pros and cons of an asymmetrical solution that involves a combination of protectionism and an outward-oriented strategy during the recovery period. It is argued that it may be more efficient than the country’s reliance on foreign loans and aid. The analysis of regional-level data for 2013-2016 lends some support to this argument.